2023
DOI: 10.1002/ps.7339
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bacillus subtilisPTA‐271 and Trichoderma atrovirideSC1 to control Botryosphaeria dieback and black‐foot pathogens in grapevine propagation material

Abstract: Background: Grapevine trunk diseases (GTDs) are a complex group of diseases that lead to major economic losses in all wine-producing countries. The investigation of biocontrol agents (BCAs) capable of forestalling or at least minimizing the development of GTDs has, recently, become a priority. Nursery experiments were set up to (i) assess the biocontrol effect of Trichoderma atroviride (Ta) SC1 and Bacillus subtilis (Bs) PTA-271, alone and in simultaneous application, against Botryosphaeria dieback (BOT)-and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Taking this into consideration, our recent work on the LC2017 product based on a low copper concentration with other substances showed a similar combined effect of Asn, fungistatic activity, and plant defense elicitor ( Mondello et al., 2021 ; Mondello et al., 2022 ). Similarly, the combination of biocontrol agents to achieve both effects is possible ( Leal et al., 2022 ). Nevertheless, the level of protection is lower compared to that of Asn, and the development of the best combination should be followed.…”
Section: Discussionmentioning
confidence: 99%
“…Taking this into consideration, our recent work on the LC2017 product based on a low copper concentration with other substances showed a similar combined effect of Asn, fungistatic activity, and plant defense elicitor ( Mondello et al., 2021 ; Mondello et al., 2022 ). Similarly, the combination of biocontrol agents to achieve both effects is possible ( Leal et al., 2022 ). Nevertheless, the level of protection is lower compared to that of Asn, and the development of the best combination should be followed.…”
Section: Discussionmentioning
confidence: 99%
“…According to the LEfSe analysis, fungal pathogens responsible to grapevine trunk diseases, like Ilyonectria, and Diaporthe [75] reduced overtime, and/or in plants inoculated with Ta SC1. In fact, previous studies have shown the effect of Ta SC1 against trunk pathogens [14,44,76], so it would be expected that Ta SC1 is able to directly antagonize pathogens in rhizosphere. However, fungi known for their biological control potential, such as Clonostachys [63], were also decreased in plants treated with Ta SC1, probably due to space and nutrients competition.…”
Section: Discussionmentioning
confidence: 99%
“…The probe sequence was 5′-/FAM/AAGCCCAAATCAAAGTCACACGTG/3IABkFQ/-3′. For Ta SC1, endochitinase gene (ech42) primers described in Savazzini et al [43] were used, and for Bs PTA-271, a DNA polymerase III gene (dnaE) primers described in Leal et al [44] were used. Each reaction contained 1× Supermix for Probes (Bio-Rad Laboratories, Hercules, CA, U.S.A.), 20 µM of each forward and reverse primer solution ( nal concentration 750 nM for each primer), 10 µM of the probe, and 2 µl of DNA template resulting in a nal volume of 20 µl.…”
Section: Droplet Digital Pcr Analysis For Bcas Absolute Quanti Cationmentioning
confidence: 99%
“…BCAs based on Trichoderma species have been successfully assayed for the control of Botryosphaeriaceae pathogens in woody crops, most of them in grapevine and Prunus spp. [36][37][38][39][40][41][42][43][44] Specifically, T. atroviride SC1 has been registered in California as a biological control agent against almond canker pathogens. 15 In addition, several bacterial strains from the genus Bacillus, Streptomyces, Pseudomonas and Xenorhabdus have demonstrated, alone or in combination with other BCAs, their antagonism against Botryosphaeriaceae species in several crops.…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition, several bacterial strains from the genus Bacillus, Streptomyces, Pseudomonas and Xenorhabdus have demonstrated, alone or in combination with other BCAs, their antagonism against Botryosphaeriaceae species in several crops. 38,40,[44][45][46][47][48][49][50][51][52] Rhizospheric bacteria have been demonstrated as potential biocontrol agents of the soil-borne pathogen M. phaseolina within the Botryosphaeriaceae family in strawberry crops. 53,54 However, to the best of our knowledge, no control agents based on bacterial strains have been successfully tested against canker diseases caused by Botryosphaeriaceae in almond.…”
Section: Introductionmentioning
confidence: 99%